2004
DOI: 10.1097/01.prs.0000142741.11963.10
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Closure of Large Lumbosacral Myelomeningoceles: The Superior Gluteal Artery Perforator Flap

Abstract: The most common form of neural tube defect is the myelomeningocele, developing during the fourth week of gestation. The era of early closure of myelomeningoceles began in the sixties with the demonstration that these patients had a lower rate of mortality. 1 The goals of early surgical closure are to (1) prevent infection, (2) eliminate cerebrospinal fluid leaks, (3) preserve neural function, and (4) diminish negative late sequelae such as pain over the closure site and possibly even tethered cord. 2 After clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…During the initial operation to harvest DICAP propeller █ DISCUSSION Plastic surgery and neurosurgery teams perform a combined operation for reconstruction of the neural tube defect and soft tissue early in the postpartum period (2). Since the introduction of perforator flaps by Koshima and Soeda in 1989, their use in reconstruction of various defects throughout the body, including myelomeningocele defects, has become widespread (2,3,17).…”
Section: Discussionmentioning
confidence: 99%
“…During the initial operation to harvest DICAP propeller █ DISCUSSION Plastic surgery and neurosurgery teams perform a combined operation for reconstruction of the neural tube defect and soft tissue early in the postpartum period (2). Since the introduction of perforator flaps by Koshima and Soeda in 1989, their use in reconstruction of various defects throughout the body, including myelomeningocele defects, has become widespread (2,3,17).…”
Section: Discussionmentioning
confidence: 99%
“…18 The surgical options available for closing a meningomyelocele defect include primary closure, 1 skin grafting, 4 local flap, 2,3,5,6,8 musculocutaneous flap, 9 -15 and fasciocutaneous flap. 16,17 Primary closure can be accomplished by undermining the wound edges in patients with a small meningomyelocele defect. Patterson and Till reported that only 14 (25%) of a group of 56 patients required more elaborate closure techniques than primary closure.…”
Section: Discussionmentioning
confidence: 99%
“…Various surgical techniques for closing a meningomyelocele defect have been reported, including a rotation flap, advancement flap, Limberg flap, bipedicled flap, musculocutaneous flap, and perforator-based flap. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We describe a new method that uses a combination flap consisting of a vertical bipedicled flap and V-Y advancement flap. This method offers several advantages compared with previously reported methods: 1) no skin grafts are needed; 2) no muscle tissue is killed; 3) it is simple and easy, leading to less blood loss and minimal operative time; and 4) it is safe and produces reliable results while eliminating wound dehiscence and skin necrosis.…”
mentioning
confidence: 99%
“…[3] Leaving a small cuff of muscle around the pedicle can be beneficial in decreasing the risk of harming the pedicle or vasospasm. Yet, caution should be taken, as leaving a cuff of muscle around the pedicle will hide small vascular branches and lead to a more bloody dissection if they go unnoticed.…”
mentioning
confidence: 99%
“…[345] Of these studies, Duffy et al . used the SGAP flap in six patients with large primary meningomyelocele defects.…”
mentioning
confidence: 99%